2022
DOI: 10.3390/microorganisms10101973
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Identification of Potential Druggable Targets in Multidrug-Resistant Acinetobacter baumannii: A Combined In Silico, In Vitro and In Vivo Study

Abstract: The remarkable rise in antimicrobial resistance is alarming for Acinetobacter baumannii, which necessitates effective strategies for the discovery of promising anti-acinetobacter agents. We used a subtractive proteomics approach to identify unique protein drug targets. Shortlisted targets passed through subtractive channels, including essentiality, non-homology to the human proteome, druggability, sub-cellular localization prediction and conservation. Sixty-eight drug targets were shortlisted; among these, glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Citric acid showed an MIC of 1.25–2.5 mg/mL, while ascorbic acid had an MIC of 3 mg/mL for all isolates. An Egyptian study [ 32 ] found that the MIC of citric acid against their Acinetobacter spp. isolates ranged from 3.25 to 1.5 mg/mL which was comparable to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Citric acid showed an MIC of 1.25–2.5 mg/mL, while ascorbic acid had an MIC of 3 mg/mL for all isolates. An Egyptian study [ 32 ] found that the MIC of citric acid against their Acinetobacter spp. isolates ranged from 3.25 to 1.5 mg/mL which was comparable to our results.…”
Section: Discussionmentioning
confidence: 99%